Legenda Meng Jiangnü: Pengarang, Perubahan Cerita dan Daya Tariknya - Wuryandari, Nurni W. (UI Scholars Hub, 2012)
The story of Meng Jiangnü, is one of the China most popular folklore-legends. Originally, it was the story of Qi Liangqi, but later transformed to Meng Jiangnü stories with many different details appeared in poems, prose romances, storytelling, or dramas. These transformations or evolutions happened due to old literary customs that made a work has possibility to be changed or recreated by many authors. The author’s creativity not only left abundant resources to interpret or analyze by scholars, but also enchanting common readers or listeners because it moral values and romanticism.